The politics of water protection - Schaub, Simon (2021)
This dissertation set out to investigate whether studying the public debates on water pollution by agricultural nitrate and contaminants of emerging concern (CECs) contributes to an enhanced understanding of differences in respective policymaking in Germany. Theoretically, the articles of this cumulative dissertation predominantly built on previous literature on public debates, discourse networks and narrative strategies. A growing literature in political science suggests that public debates influence policymaking processes in democratic systems and has shown that analyzing public debates contributes to a better understanding of observed variation in policy outcomes. Empirically, the articles investigated public debates and policymaking on two cases of water pollution in Germany: nitrate water pollution caused by agricultural activities and CECs with special attention on pharmaceutical contaminants. Both cases varied regarding the characteristics of the public debates and the policy outcomes. The debate on agricultural nitrate water pollution became increasingly polarized over time and coincided with a significant change in fertilizer regulation, whereas the persistence of comparatively liberal regulation on CECs was accompanied by a non-polarized and largely non-disputed public debate. The four articles of this cumulative dissertation are structured into two parts. In the first part, two articles engaged with the empirical case of agricultural pollution of water. The first article investigated the public debate on agricultural nitrate pollution. More specifically, it analyzed whether political actors used narrative strategies to influence policymaking. The second article focused on German political parties and investigated whether their attention and positioning on agricultural pollutants in water was associated with policymaking on the issue. In the second part, the two articles shed light on the public debate on water pollution by CECs. The first article explained the policy outcome on pharmaceutical contaminants by examining the German public debate on the issue. The second article compared the approach of discourse and policy networks and their respective empirical findings on the issue of CECs. Overall, the dissertation makes several theoretical, methodological and empirical contributions to literature on public debates, policy narratives, agenda-setting, policy integration, social network analysis, and the issue of water pollution in Germany.